Small-area moving ratios and the spatial connectivity of neighborhoods: Insights from consumer credit data: - Daepp, Madeleine (Environment and Planning B: Urban Analytics and City Science, 2021)
Communities share challenges with the neighborhoods to which former residents move and the neighborhoods from which new residents arrive. A lack of migration data for small geographic areas, howeve...